Uji Efektivitas Jamur Beuveria bassiana dalam Mengendalikan Hama Walang Sangit (Leptocorisa acuta) pada Tanaman Padi - I Wayan Juliartawan; Ida Bagus Komang Mahardika; Anak Agung Sg Putri Risa Andriani (GEMA AGRO, 2022)
The purpose of this study was to determine the effectiveness of the Beauveria bassiana fungus in controlling the pest and to determine the best concentration of Beauveria bassiana to control the pest. This research was carried out at the Pest and Disease Observation Laboratory (LPHP) at the Bali Province Food Crops and Horticulture Protection Center (BPTPH) from November 2020 to october 2021. This study used a completely randomized design (CRD). With a level of 5 concentrations, the concentration treatment was B1 = 2 ml Beauveria bassiana . liter-1 water, B2 = 4 ml Beauveria bassiana . liter-1 water, B3 = 6 ml Beauveria bassiana . liter-1 water, B4 = 8 ml Beauveria bassiana . liter-1 water, B5 = 10 ml Beauveria bassiana . liter-1 of water. The results showed that in the treatment with a concentration of 10 ml Beauveria bassiana . liter-1 Liter of water, the mortality percentage was 100%, which was not significantly different from the treatment with 8 ml of Beauveria bassiana . liter-1 of water with a mortality percentage of 97,5% and significantly different. with other treatments.